Knowledge on Nutrition Labels for Processed Food: Effect on Purchase Decision among Indonesian Consumers - Mauludyani, Anna Vipta Resti; Nasution, Zuraidah; Aries, Muhammad; Rimbawan, Rimbawan; Egayanti, Yusra (Jurnal Gizi dan Pangan, 2021)
This study was conducted to observe the relationship between consumers’ knowledge on nutrition labels and the purchasing behavior for processed food products among Indonesian consumers. A crosssectional study was conducted in August‒September 2018 in five different cities of three provinces (Jakarta, Bogor, Depok, Tangerang, and Bekasi). Data were obtained from 400 adult consumers by self-administered questionnaires. The results showed that almost 70% of consumers in Indonesia check food labels; however, from that number only 37.5% paid attention to the nutrition label of a food product prior to making a purchase decision; this was most probably due to their knowledge on nutrition labels that was still poor, as shown by the mean score of 7.7 out of 14 questions (55%). In terms of food groups, milk and dairy products were deemed important by the consumers and the nutrition labels were often checked. When it comes to making a purchase decision, almost all of the consumers (96.0%) had decided to buy food products with nutrition labels as compared to those without. Furthermore, when compared to similar products also bearing nutrition labels, consumers deemed the claims of low fat (28.7%) and low sugar (22.6%) as a sign that the products are healthier and have a better nutrition profile. Knowledge on nutrition labels (OR=1.139; 95% CI:1.016‒1.276; p=0.025) and purchase decision on products with nutrition labels (OR=3.426; 95% CI:1.220‒9.623; p=0.019) were significantly associated with purchase decision for healthier processed food. This study has shown the importance of increasing consumers’ knowledge on nutrition labels in order to achieve a larger impact on food selection, nutrition, and health.